720 Angiography-derived index of microvascular resistance (IMR-angio) in Takotsubo syndrome. (8th December 2021) - Castaldi, Gianluca; Fezzi, Simone; Widmann, Maddalena; Mammone, Concetta; Rizzetto, Francesca; Lia, Micaela; Prati, Daniele; Pighi, Michele; Pesarini, Gabriele; Tavella, Domenico; Scarsini, Roberto; Ribichini, Flavio
Abstract: Aims: Coronary microvascular dysfunction (CMD) has been proposed as a key driver in the etiopathogenesis of Takotsubo syndrome (TTS), likely related to an 'adrenergic storm' upon a susceptible microvascular circulation. The aim of our manuscript was to assess and quantify coronary microvascular disfunction in patients with TTS using the recently developed angiography-derived index of microcirculation (IMRangio) and evaluate its correlation with clinical and instrumental presentation. Methods and results: 41 consecutive TTS patients were retrospectively analysed. Three different formulas for compute non-hyperemic IMRangio (NH-IMRangio) derived by 3D-Quantitative Coronary Angiography (3D-QCA) and Quantitative Flow Reserve (QFR) analysis were used according to each fluidodynamic mathematical expression as reported by respective authors. CMD was deﬁned as an IMRangio ≥25. Moreover, correlation between NH-IMRangio and clinical presentation and a comparation between the three formulas were provided. Median age was 76 years, 85.7% were women and mean LVEF at first echocardiogram was 41.2%. All patients presented CMD with NH-IMRangio ≥25 in at least one territory. Mean NH-IMRangio was higher in Left Anterior Descending artery (LAD) than Circumflex artery (CX) and Right Coronary artery (RCA) with either Oxford-NH-IMRangio (52.7 ± 18.6 vs. 35.3 ± 13.6 vs. 41.4 ± 15.1, P -value < 0.001), Madrid-NH-IMRangio (47.2 ± 17.3 vs. 31.8 ± 12.2 vs. 37.3 ± 13.7, P -value <0.001) or Ferrara-NH-IMRangio (52.7 ± 19 vs. 36.1 ± 14.1 vs. 41.8 ± 16.1, P -value < 0.001). Furthermore, the mean values of NH-IMRangio were not significantly different using the different equations (OXFvsMAD P -value = 0.1930; OXFvsFER P -value = 0.9609; MADvsFER P -value = 0.2144). NH-IMRangio in LAD territory was significantly higher in pts presenting with LVEF impairment (≤40%) than pts with preserved ventricular global function (mean NH-IMRangio LAD 59.3 ± 18.1 vs. 46.3 ± 16, P -value = 0.030). NH-IMRangio assessed in LAD territory showed a trend towards linear association with LVEF (Figure 1). Conclusions: CMD, assessed with NH-IMRangio, is a common finding in TTS and it is associated with LVEF dysfunction and LVEF recovery. The validated formulas for NH-IMRangio computation have a superimposable diagnostic performance and accuracy.